The Role Of Effective Introduction In Enhancing Audience Engagement - Nisrina Farida Ramadhanti; Hesty Widiastuty; Cahaya Ningrum; Nur Lutfiah (Journal of Innovative and Creativity, 2025)
Openness in public speaking has an important role in determining how well the message is conveyed and how deeply the audience engages. An effective opening not only makes a positive first impression but also builds credibility and creates an emotional connection with the listener. However, many previous studies have placed more emphasis on speaking ability in general without specifically analyzing how opening components such as attention-grabbing, relevance, credibility, and summary systematically affect audience engagement. Therefore, this study aims to conceptually examine the role of effective openings in increasing audience engagement through the Conceptual Literature Review (CLR) approach. This analysis integrates perspectives from communication studies, applied linguistics, and educational psychology to develop a comprehensive understanding of how openness affects the cognitive, emotional, and behavioral dimensions of engagement. This review identified that a well-crafted introduction can grab the audience's attention, build empathy, and encourage responses throughout the presentation. These findings emphasize that an introduction is not just a structural element but a strategic tool that determines the success of communication. Furthermore, this study demonstrates pedagogical implications for public speaking teaching, suggesting that teachers guide students in designing openings that are cognitively and emotionally connected to their audiences. Overall, effective openings serve as a driving force that turns passive listeners into active participants, underscoring that engagement in communication begins from the moment the speaker begins speaking.